Предмет: Алгебра,
автор: MarryKy
Помогите решить логарифмическое уравнение
Приложения:
Ответы
Автор ответа:
0
log_2 (x^3 - 1) - log_2 (x^2 + x + 1) = 4
log_2 [(x^3 - 1) / (x^2 + x + 1]) = 4
(x^3 - 1) / (x^2 + x + 1] = 16
[(x - 1) * (x^2 + x + 1)] / ( x^2 + x + 1) = 16
x - 1 = 16
x = 17
log_2 [(x^3 - 1) / (x^2 + x + 1]) = 4
(x^3 - 1) / (x^2 + x + 1] = 16
[(x - 1) * (x^2 + x + 1)] / ( x^2 + x + 1) = 16
x - 1 = 16
x = 17
Похожие вопросы
Предмет: Другие предметы,
автор: binaliabdullaev13
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Nikitovskij2010
Предмет: Физика,
автор: fleur565
Предмет: Физика,
автор: Эсфер